Design and validation of a 6-Port Planar MIMO array for sub-6 GHz 5G bands - Hossain, A K M Zakir; Ibrahimy, Muhammad Ibn; Nor, Mohd Khanapiah; Dahalan, Abdul Halim (Seventh Sense Research Group, 2024)
This article proposes the design, fabrication, and experimental validation of a six-port (6×6) modified planar rectangular MIMO antenna array for mid-band 5G smartphone applications. The proposed array operates over a frequency range of 2.63 GHz to 6.64 GHz, achieving a bandwidth of approximately 85% centered at 4.63 GHz, covering essential sub-6 GHz 5G bands. The array's isolation between ports is primarily maintained below -20 dB, ensuring minimal mutual coupling. The Realized Gain (RG) ranges from 4 to 6 dBi, while the Total Efficiency (TE) reaches up to 80%. Furthermore, the Envelope Correlation Coefficient (ECC) remains as low as 0.002, and the Diversity Gain (DG) is nearly constant at 10 across the operating bandwidth. The Specific Absorption Rate (SAR) values are well below regulatory limits, with the lowest measured at 0.175 W/kg and the highest at 1.27 W/kg, ensuring safe usage for mobile applications.